Cerebral Ischemia-Reperfusion Is Associated With Upregulation of Cofilin-1 in the Motor Cortex - Xu, Ming-Shu; Yin, Lei-Miao; Cheng, Ai-Fang; Zhang, Ying-Jie; Zhang, Di; Tao, Miao-Miao; Deng, Yun-Yi; Ge, Lin-Bao; Shan, Chun-Lei (Frontiers in Cell and Developmental Biology, 2021)
Cerebral ischemia is one of the leading causes of death. Reperfusion is a critical stage after thrombolysis or thrombectomy, accompanied by oxidative stress, excitotoxicity, neuroinflammation, and defects in synapse structure. The process is closely related to the dephosphorylation of actin-binding proteins (e.g., cofilin-1) by specific phosphatases. Although studies of the molecular mechanisms of the actin cytoskeleton have been ongoing for decades, limited studies have directly investigated reperfusion-induced reorganization of actin-binding protein, and little is known about the gene expression of actin-binding proteins. The exact mechanism is still uncertain. The motor cortex is very important to save nerve function; therefore, we chose the penumbra to study the relationship between cerebral ischemia-reperfusion and actin-binding protein. After transient middle cerebral artery occlusion (MCAO) and reperfusion, we confirmed reperfusion and motor function deficit by cerebral blood flow and gait analysis. PCR was used to screen the high expression mRNAs in penumbra of the motor cortex. The high expression of cofilin in this region was confirmed by immunohistochemistry (IHC) and Western blot (WB). The change in cofilin-1 expression appears at the same time as gait imbalance, especially maximum variation and left front swing. It is suggested that cofilin-1 may partially affect motor cortex function. This result provides a potential mechanism for understanding cerebral ischemia-reperfusion.